Prevalencia de infertilidad femenina en Cuba, 2018. / Prevalence of female infertility in Cuba, 2018. - Ramón Suárez Medina; Sonia Bess Constantén; Rogelio González Sánchez (Universidad de La Habana, 2022)
Introduction: International data on the prevalence of infertility are not very exact, with important geographical differences, which are explained by environmental, cultural and socioeconomic influences. Few studies have been carried out in Cuba and none on a large scale. Objective: To determine the prevalence of female infertility in Cuba. Methods: A specific questionnaire was applied to 16,500 women between the ages of 15 and 49 in the period from January to December 2018, belonging to 39 health areas and 330 family doctor's offices. The non-equiprobabilistic design took in to account the population reported in the Demographic Yearbook of Cuba, 2017. The prevalence ratios and their 95% confidence intervals were calculated, using the Wald test and its associated p-value for the significance of the coefficients. Results: The prevalence at the country level was estimated at 4.0% of women of child bearing age, being 4.0% in urban areas and 3.6% in rural areas, higher in the central region and lower in the eastern region. The prevalence of primary infertility was estimated at 1.1% and secondary at 2.9%. In infertile women, the mean age was 30 years for primary and 34 for secondary, at the time of diagnosis the age was 38 years. White skin color predominated, high educational level. Conclusions: It was estimated that the prevalence of female infertility in Cuba is 4.0% of women of child bearing age. / RESUMEN Introducción: Los datos internacionales sobre prevalencia de la infertilidad no son muy exactos, con importantes diferencias geográficas, que se explican por las influencias ambientales, culturales y socioeconómicas. En Cuba se han desarrollado pocos estudios y ninguno a gran escala. Objetivo: Determinar la prevalencia de la infertilidad femenina en Cuba. Métodos: Se aplicó un cuestionario específico a 16 mil 500 mujeres de entre 15 y 49 años en el período de enero a diciembre del año 2018, pertenecientes a 39 áreas de salud y 330 consultorios del médico de familia. El diseño no equiprobabilístico tuvo en cuenta la población reportada en el Anuario Demográfico de Cuba y sus territorios, 2017. Se calcularon las razones de prevalencia y sus intervalos de confianza del 95%, usándose para la significación de los coeficientes la prueba de Wald y su valor p asociado. Resultados: Se estimó la prevalencia a nivel de país en el 4,0 % de las mujeres en edad fértil, siendo 4,0 % en zona urbana y 3,6 % en la rural, más elevada en la región central y más baja en la oriental. La prevalencia de infertilidad primaria fue estimada en 1,1 % y la secundaria en 2,9 %. En mujeres infértiles la edad media fue de 30 años para la primaria y 34 para la secundaria, al momento del diagnóstico la edad fue 38 años. Predominó el color de piel blanco, elevado nivel educacional. Conclusiones: Se estimó que la prevalencia de infertilidad femenina en Cuba es el 4,0 % de las mujeres en edad fértil.